Do higher corporate taxes reduce wages? Micro evidence from Germany - Clemens Fuest; Andreas Peichl; Sebastian Siegloch (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
Because of endogeneity problems very few studies have been able to identify the incidence of corporate taxes on wages. We circumvent these problems by using an 11-year panel of data on 11,441 German municipalities' tax rates, 8 percent of which change each year, linked to administrative matched employer-employee data. Consistent with our theoretical model, we find a negative effect of corporate taxation on wages: a 1 euro increase in tax liabilities yields a 77 cent decrease in the wage bill. The direct wage effect, arising in a collective bargaining context, dominates, while the conventional indirect wage effect through reduced investment is empirically small due to regional labor mobility. High and medium-skilled workers, who arguably extract higher rents in collective agreements, bear a larger share of the corporate tax burden.
urn:nbn:de:bsz:180-madoc-339218; More recent version: http://hdl.handle.net/10419/125812
Keywords: H2; H7; J3; 330; business tax; wage incidence; administrative data; local taxation